Drivers of Social Media Marketing Adoption and Performance Impacts on Indonesian SMEs: An Integrated TAM, RDT, and TOE Framework - Lukitaningsih, Ambar; Fadhilah, Muinah; Kusumawardhani, Ratih (Journal of Ecohumanism, 2024)
This study explores the drivers of social media marketing (SMM) adoption and its impact on the financial performance of small and medium-sized enterprises (SMEs) in Indonesia. Using an integrated framework combining the Technology Acceptance Model (TAM), Resource Dependence Theory (RDT), and Technology-Organization-Environment (TOE) frameworks, the research investigates how internal, external, and organizational factors influence the adoption of social media marketing. Data were collected from 300 SME owners and managers and analyzed using descriptive statistics and structural equation modeling (SEM-PLS). The findings reveal that perceived usefulness, competitive pressure, and government support are significant drivers of SMM adoption. Moreover, the study highlights that adopting social media marketing positively impacts SMEs’ financial performance, increasing sales, customer engagement, and profitability. The research also identifies barriers hindering SMM adoption, such as financial costs and lack of human resources. This study offers valuable insights for policymakers and business leaders seeking to enhance the digital competitiveness of SMEs, particularly in emerging markets like Indonesia. It contributes to the existing literature by empirically linking SMM adoption to financial outcomes and providing a holistic view of the factors influencing adoption. The findings set a benchmark for future research on technology adoption in SMEs within similar contexts..